Power system fault diagnosis using artificial neural network (ANN) / Mohb Ashraf Mohd Zain - Mohd Zain, Mohb Ashraf (2010)
In power system, the phenomenon of fault is a name given to a situation called a failure in the system. Most faults are the results of short circuits which include thunder and wind of storms. Faults are the major concern in power generation, transmission and distribution since they occur frequently and without warning. The classification of the transmission line faults which are bus voltage, fault and line current are very useful in monitoring and performance of relays, circuit breakers and other protection and control element.